Contributions to a Brazilian Code of Conduct for Fieldwork in Geology: an approach based on Geoconservation and Geoethics - KÁTIA L. MANSUR; LUIZA C.M.O. PONCIANO; ALINE R.S.F. DE CASTRO (Anais da Academia Brasileira de Ciências)
ABSTRACT When considering the numerous events that have prohibited the development of scientific projects or caused destruction of outcrops, it is clear that there is rapidly increasing necessity to define a Brazilian Code of Conduct for geological fieldwork. In general, this destruction is attributed to lack of knowledge as to the relevance of geological sites. The aim of this Code of Conduct is to guide geologists to adopt good practices during geoscience activities. Proposed guidelines are based on Codes of Conduct from other countries, mainly Scotland and England, on situations described in papers and on the personal experience of the authors. In this paper 29 points are suggested, in order to guarantee that fieldwork is conducted in accordance with geoethics, geoconservation and sustainability values. The proposal is structured in three parts: (1) Behavior and practices in respect to local traditions and providing information to the population; (2) Measures to minimize degradation on outcrops; and (3) Safety. The proposal seeks to broaden the debate on the need for responsible behavior during fieldwork, in order to promote respect for geodiversity. Through this code, Brazilian geoscientists will be able to contribute to the conservation of geological heritage and of outcrops with special educational relevance.